And Everything Emptying into White: Interview and Biography in I Was Born to Be Brief (2020)
This article proposes a reading on Nací para ser breve, by Gabriela Massuh, as a text that  is part of what Roland Barthes called "biographical nebula", in other words, a text that even without being a proper biography or an autobiography works with the writing of real lives. One of the hypothesis of this article is that the interview –the book is mainly a long interview that the author made to María Elena Walsh in 1981, while Walsh was recovering from cancer– is a possible way of recounting a person’s life. Furthermore, because of the way the book was made, this article entails that silence and death are part of this making process. Therefore, Nací para ser breve emphasizes its links very closely with the “deathbed scenes” and with the so-called "last interviews". Finally, focusing on the transcription of the interview, this article brings out some hypotheses in regard to the problem of the voice –understood as sound, as phoné– in the biographical writing.